Strengthening Integrated Care in Central and Eastern Europe - Somanathan, Aparnaa; Finkel, Elyssa; Arur, Aneesa (World Bank, Washington, DC, 2020)
The objective of this report is to provide guidance on the design and implementation of service delivery models that promote integration of care. Specifically, the report seeks to (i) systematically review the main reform levers of integrated care; (ii) identify processes needed to create an enabling environment for the implementation of integrated care; and (iii) provide guidance on sequencing the different levers and support strategies. This report builds on the findings of recent work that systematically analyzes well-functioning integrated programs in the European Union, North America, and elsewhere, as well as five case studies in Croatia and Poland that were carried out as part of this report.